2021
DOI: 10.1002/eji.202049101
|View full text |Cite
|
Sign up to set email alerts
|

Peptide microarray‐based analysis of antibody responses to SARS‐CoV‐2 identifies unique epitopes with potential for diagnostic test development

Abstract: Humoral immunity to the Severe Adult Respiratory Syndrome (SARS) Coronavirus (CoV)‐2 is not fully understood yet but is a crucial factor of immune protection. The possibility of antibody cross‐reactivity between SARS‐CoV‐2 and other human coronaviruses (HCoVs) would have important implications for immune protection but also for the development of specific diagnostic ELISA tests. Using peptide microarrays, n = 24 patient samples and n = 12 control samples were screened for antibodies against the entire SARS‐CoV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 39 publications
15
52
1
Order By: Relevance
“…Thus, we focused on RBD, due to the capacity of RBD protein vaccines to induce strong neutralizing antibody titres [ 21 ]. The poor identification of linear B-cell epitopes using 15-mer peptides [ 38 ], as opposed to results obtained with longer peptides [ 24 , 39 ], forced us to adopt an alternative mapping strategy. In this way we found that half of the tested peptides were immunogenic, and that some of them induced antibodies that recognized the original protein, validating this approach [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we focused on RBD, due to the capacity of RBD protein vaccines to induce strong neutralizing antibody titres [ 21 ]. The poor identification of linear B-cell epitopes using 15-mer peptides [ 38 ], as opposed to results obtained with longer peptides [ 24 , 39 ], forced us to adopt an alternative mapping strategy. In this way we found that half of the tested peptides were immunogenic, and that some of them induced antibodies that recognized the original protein, validating this approach [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent advances in omics-type approaches present opportunities for in-depth immunological analysis of clinical samples and ex vivo cell cultures, which have not previously been possible due to the remote field location of these trials [117]. Moreover, epitope-mapping techniques can be used with serum collected from vaccinated and putatively immune animals to identify specific natural-and vaccine-induced epitopes displaying a high degree of immunogenicity and associations with protective immunity for further research and development [118,119].…”
Section: Vaccine Trials Against Natural Infection With O Ochengi In Cameroonmentioning
confidence: 99%
“…By combining clinical information, IgG/IgM immune responses and blood parameters, we established a database (COVID-ONE-hi) that provides a one-stop analysis pipeline for COVID-19 specific immune responses and clinical parameters ( Figure 1 B). To help users obtain more COVID-19 serum profiling data, we set up a page on the COVID-ONE-hi website, named “More studies”, to archive other highly related data of COVID-19 serum profiling (protein/peptide microarray/phage display) [ [14] , [15] , [16] , [17] , [18] , [19] ]. In addition, a healthy control dataset was added to the HELP page, which contains the IgG and IgM responses for 528 healthy people against the 21 proteins and spike protein peptides (Table S2).…”
Section: Database Content and Usagementioning
confidence: 99%